JUMLAH CEMARAN BAKTERI Escherichia coli PADA DAGING KAMBING DI PASAR TRADISIONAL KOTA BANDA ACEH The Amount Of Bacteria Escherichia coli Feed On Goat Meat At Traditional Market Banda Aceh City - Della Miranti; ismail ismail; razali razali (JURNAL ILMIAH MAHASISWA VETERINER, 2017)
Penelitian ini bertujuan untuk mengetahui jumlah cemaran bakteri Escherichia coli pada daging kambing di pasar tradisional kota Banda Aceh. Sampel penelitian adalah berasal dari bagian daging paha atas. Pengambilan sampel dilakukan secara acak di 5 pasar tradisional kota Banda Aceh, yaitu Pasar Peunayong, Pasar Beurawe, Pasar Seutui, Pasar Ulee Kareng, dan Pasar Gampong Baru. Setiap pedagang diambil satu sampel bagian daging paha atas dan dimasukkan kedalam plastik steril lalu dimasukkan kedalam kotak pendingin. Metode Pengujian dilakukan melalu identifikasi di laboratorium dengan metode hitungan cawan total/Total Plate Count. Identifikasi E.coli menggunakan media selektif dengan metode dari agar khusus Eosin Methylen Blue Agar. Data yang diperoleh dianalisis secara deskriptif. Dari hasil penelitian didapat bahwa jumlah bakteri Escherichia coli pada daging kambing di pasar Peunayong adalah 2,5 x 102, pasar Beurawe adalah negatif, pasar Gampong Baru adalah 2,8 x 102, pasar Seutui adalah 4,9 x 102 dan pasar Ulee Kareng adalah 3,5 x 102. Semua sampel daging kambing tercemar Escherichia coli, yang memperlihatkan perubahan koloni berwarna metalik kehijauan pada Eosin Methylen Blue Agar. Dari penelitian ini dapat disimpulkan jumlah cemaran bakteri pada daging kambing pada pasar tradisional di Banda Aceh besar tidak memenuhi standar SNI. SNI 01-7388-2009.This study aims to determine the amount of contamination of Escherichia coli bacteria in goat meat in the traditional market of Banda Aceh city. The study sample was derived from the upper thigh meat section. Sampling was conducted randomly in 5 traditional markets of Banda Aceh, namely Peunayong Market, Beurawe Market, Seutui Market, Ulee Kareng Market, and Pasar Gampong Baru. Each merchant picked up a sample of the upper thigh meat section and inserted into a sterile plastic then inserted into the cooler. Testing method is done through the identification in the laboratory with the Total Plate Count method. Identification of E.coli using selective media with a method of special agar Eosin Methylen Blue Agar. The data obtained were analyzed descriptively. From the research results, it is found that the number of Escherichia coli bacteria in goat meat in Peunayong market is 2.5 x 102, Beurawe market is negative, New Gampong market is 2.8 x 102, Seutui market is 4.9 x 102 and Ulee Kareng market is 3.5 x 102. All samples of mutton contaminated Escherichia coli, which showed a greenish-colored colony change in Eosin Methylen Blue Agar. From this research, it can be concluded that the amount of bacteria contamination in goat meat in traditional market in Banda Aceh does not meet the standard of SNI. SNI 01-7388-2009. This study aims to determine the amount of contamination of Escherichia coli bacteria in goat meat in the traditional market of Banda Aceh city. The study sample was derived from the upper thigh meat section. Sampling was conducted randomly in 5 traditional markets of Banda Aceh, namely Peunayong Market, Beurawe Market, Seutui Market, Ulee Kareng Market, and Pasar Gampong Baru. Each merchant picked up a sample of the upper thigh meat section and inserted into a sterile plastic then inserted into the cooler. Testing method is done through the identification in the laboratory with the Total Plate Count method. Identification of E.coli using selective media with a method of special agar Eosin Methylen Blue Agar. The data obtained were analyzed descriptively. From the research results, it is found that the number of Escherichia coli bacteria in goat meat in Peunayong market is 2.5 x 102, Beurawe market is negative, New Gampong market is 2.8 x 102, Seutui market is 4.9 x 102 and Ulee Kareng market is 3.5 x 102. All samples of mutton contaminated Escherichia coli, which showed a greenish-colored colony change in Eosin Methylen Blue Agar. From this research, it can be concluded that the amount of bacteria contamination in goat meat in traditional market in Banda Aceh does not meet the standard of SNI. SNI 01-7388-2009.